Evaluation of inoculant-treated corn silages - Bolsen, K.K.; Tiemann, D.G.; Sonon, R.N.; Hart, R.A.; Dalke, B.; Dickerson, J.T.; Lin, C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Whole-plant corn silages treated with either Pioneer 1174® or Biotal® inoculants were preserved more efficiently than control silages. They had slightly higher dry matter (DM) recoveries; more lactic acid; higher lactic to acetic acid ratios; and less acetic acid, ethanol, and ammonia-nitrogen. Laboratory silo results showed that both inoculated silages produced lactic acid faster than control silages during the first 7 days and had more desirable fermentation profiles at the end of 90 days. Applying 5 or 10 times the recommended rate of Biotal inoculant had only a small and nonsignificant effect on rate and efficiency of fermentation. Yearling steers fed the two inoculated corn silages gained numerically but not significantly faster and more efficiently than steers fed control silages, so inoculated silages produced about 6.1 lb more steer gain per ton of crop ensiled than controls.
Keywords: Beef; Silage; Bacterial; Inoculants; Corn